Simulation of water photo electrolysis with III-nitride semiconductor nano wires - Witzigmann, Bernd; Bettenhausen, Maximilian; Mewes, Marvin; Fuele, Heiko; Roemer, Friedhard (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
Water splitting under illumination with a GaN/InGaN planar and nano wire structure is modeled using a drift diffusion approach. The main features of the experiment such as current density without biasing and current saturation effects are explained by the simulation. The electrolyte where ionic transport occurs is modeled as material with diffusion coefficients matching ionic diffusivity experiments. The simulation allows design and analysis of GaN based nano structures and their water photo electrolysis efficiency. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Energy Harvesting; Gallium Nitride; Nano Wire; Simulation; Water Splitting